Allegories of Union in Irish and English writing, 1790-1870 : politics, history, and the family from Edgeworth and to Arnold - Corbett, Mary Jean, 1962- (Cambridge University Press, 2000)
Corbett explores fictional and non-fictional representations of Ireland's relationship with England throughout the nineteenth century. She situates her readings of novels by Edgeworth, Gaskell, and Trollope, and writings by Burke, Engels, and Mill, within the historical contexts that shape them, offering a fresh perspective on important aspects of Victorian culture.